PRODUKTIVITAS PERTANIAN: SUATU TELAAH PUSTAKA - bhenu SE artha; Niken Permata Sari; Ardhi Khairi (Fakultas Sains Terapan, Universitas Suryakancana Cianjur, 2022)
Farm productivity is influenced by many things. Climate change is an important environmental issue that disrupts global agricultural production, especially where agriculture is the main activity. Adoption of agricultural technology is an important resource for increasing sustainable crop production. This study aims to determine the variables associated with farm productivity. This research is a literature study that uses 12 research articles as references. The results showed that there were no variables that were influenced by farm productivity. Further research can examine this matter.